Effect of kangaroo mother care on serum bilirubin levels in term neonates undergoing phototherapy for neonatal jaundice: a cross-sectional study in South India - Pasha, Touheer; R., Afraneha; Prasad, Krithika; Ramesh, Shanthi (International Journal of Research in Medical Sciences, 2025)
Background: Neonatal jaundice is a common condition affecting nearly 60% of full-term and 80% of preterm infants, characterized by elevated serum bilirubin levels. While most cases resolve without intervention, untreated hyperbilirubinemia can result in serious neurological complications such as kernicterus. Phototherapy is the standard treatment but may lead to adverse effects and prolonged hospitalization. Kangaroo mother care (KMC), involving skin-to-skin contact between infant and caregiver, has emerged as a supportive, cost-effective method that may enhance bilirubin clearance and improve recovery. Objective is to evaluate the effect of KMC on serum bilirubin levels in term neonates with jaundice undergoing phototherapy. Methods: A cross-sectional observational study was conducted over one year (July 2023 to August 2024) in the Department of Paediatrics at Sree Balaji Medical College and Hospital. A total of 120 term neonates (gestational age 37–42 weeks; birth weight >2500 g) with neonatal hyperbilirubinemia requiring phototherapy were included using purposive sampling. Exclusion criteria were preterm birth, low birth weight, early-onset jaundice, hemolytic disorders, and congenital anomalies. Participants were divided into two groups: phototherapy alone and phototherapy with KMC. Serial bilirubin levels were measured at baseline, 24, 48, and 72 hours, and at the end of treatment. Statistical analysis was performed using SPSS v27 with chi-square tests, correlation analysis, and Bland-Altman plots. Results: Infants receiving KMC alongside phototherapy showed significantly faster bilirubin reduction (p<0.05) compared to those receiving phototherapy alone. No significant association was found with infant gender or maternal age. However, higher gestational age and maternal education were positively correlated with improved outcomes. The KMC group demonstrated enhanced clinical recovery without adverse effects. Conclusions: KMC is an effective adjunct to phototherapy in managing neonatal jaundice. It accelerates bilirubin clearance, and may offer added benefits such as improved bonding and lower healthcare costs. KMC should be considered in routine neonatal care, especially in low-resource settings. Further research is needed to explore its long-term outcomes.